A naturalistic, observational study of the Seven-Eyed model of supervision. Issue 1 (2nd January 2022) - McMahon, Aisling; Jennings, Ciaran; O'Brien, Gillian
ABSTRACT: In this observational study, recordings of 40 individual supervision meetings over six months for five supervisory dyads in an Irish, transdisciplinary youth mental health service were analyzed and illustrated according to the Seven-Eyed model of supervision. Results offer empirical support regarding the model's relevance for supervision practice, provide practice-based evidence to elaborate aspects of the model, and show the model's value in identifying areas of practice that may benefit from development. Illustrations of some supervision exchanges are shared which contribute to our understanding of the complexity of working at the personal-professional boundary, particularly in workplace, transdisciplinary supervision involving dual roles.